NANOTECHNOLOGY AND SPORT - Zoran Mašić; Milan Mihajlović; Filip Radotić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
We can say that sports are continuously evolving. To improve the quality of this work, changes are being made in all of these segments: development and selection of athletes, the improvement of technology for preparation and performance tactics, training methods for relaxation. On the other hand these are followed by rule changes, modern sports facilities, as well as legal regulations. One direction in the improvement of sports results is an attempt at rational spending of existing resources for athletes, regardless of whether in team or individual sports. Nanotechnology is also contributioning toward this direction. This paper points out the appearance of nanotechnology, its essence, i.e., the way it may effect the development of sports. Of course, it also points to the potential risk of applying nanotechnology to sports.